Usability Evaluation For Child Development Website Interface - Srirahayu, Agustina; Dwi Radita, Kurnia (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
This study aims to evaluate the usability of the child development website interface using the usability testing method. The evaluation was conducted by involving 20 participants consisting of parents and caregivers of children, who were asked to complete a series of tasks on the website. The assessment was carried out based on five main dimensions of usability: learnability, efficiency, memorability, errors, and satisfaction. The results showed that the website had good learnability, with the majority of participants being able to understand the interface on first use. User satisfaction was also high, with an average score of 4 out of 5. However, some problems were found in terms of efficiency, especially related to navigation which sometimes required too many steps. In addition, the level of user error increased on more complex tasks, such as using child development aids, which required clearer instructions. These findings provide recommendations for improving the usability of the website, including simplifying navigation, providing more comprehensive guidance, and improving feedback from the system. Implementation of these improvements is expected to increase the effectiveness of the website in helping parents monitor their child's development more efficiently.